Notice for Project Director, BRAC University new campus project to submit financial proposal as a single source for the procurement of goods, works and services mentioned in this letter for BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding notice for Project Director, BRAC University new campus project to submit financial proposal as a single source for the procurement of goods, works and services mentioned in this letter for BRAC University new campus project.